PERSPEKTIF EKONOMI KELEMBAGAAN: EKONOMI KOLEKTIF PEREMPUAN PERAJIN ANYAMAN BAMBU (Magister Manajemen Universitas Wisnuwardhana, 2021)
The activities of the people of Kayubihi Village, Bangli Regency, Bali Province, Indonesia, especially housewives, have traditionally preserved the ancestral culture of making woven bamboo. The woven bamboo produced is done individually or in groups. The bamboo used to make the wicker is obtained from the artisans' own gardens and also purchased from neighboring villages. This study aims to determine (1) the system of shared resource management, (2) production activities. This research includes qualitative research with a grounded research approach, with a gradual analysis with a systematic approach from Strauss and Corbin. The research subjects are women who are bamboo weaving craftsmen, the data collection procedure is through observation and interviews. From the data analysis, it is known that the system manages shared resources based on considerations in the availability of raw materials, the relationship between the coordinator and the craftsmen as well as trust and solidarity. The existing production activities when making woven bamboo by craftsmen are seen from productivity and creativity.